The cognitive styles (CSI) in students of higher education in a city in Southern Chile - Rivera, Felipe; Velázquez, Julio; Sánchez, Carolina (Journal of Learning Styles, 2019)
There is evidence of concern, both in the research and educational practices, as to evaluating cognitive and learning aspects in higher education, particularly in the variable learning styles. However, the research development have not considered instruments that count with psychometric support. This way, it is relevant to incorporate in the measurement an instrument that contains the construct cognitive styles, understood as a characteristic involved in learning, along with optimal psychometric properties, being The Cognitive Style Index (CSI) of Allinson and Hayes suitable for this purpose. The objetive of this research has been to adapt the CSI instrument to the higher education population of a city in southern Chile.Through inverse translation, Alpha de Cronbach and Confirmatory Factor Analysis (AFC), linguistic equivalence, adequate reliability and construct validity were confirmed. From the psychometric evidence shown, the CSI is placed as an appropriate instrument to identify and describe the Cognitive Style as a relevant tool to show students characteristics and their way of learning, in the context of future research.
Keywords: Cognitive Styles; Psychometry; Adaptation; Higher Education